The origin and development of law in Ancient Rome (middle of the VIII–VI centuries B.C.) - Pylypchuk, O. O. (History of science and technology, 2018)
The article covers the history of the formation of Roman law in the "period of kings" in the context of the development of Rome from ancient times to the time of the formation of the republic. The formation of the social-political system, the division of the Roman population into genuses and families, the formation of social classes of patricians, plebeians and proletarians, the centralization of power in the hands of an elected monarch, the administration of the state through the Senate, the formation of a troop divided into centuries, which subsequently turned into a separate social stratum that became representative of the interests of the people and had a tremendous impact on the state power of the country. It describes the formation of concepts of positive and sacred law, each of which had its own sphere of influence and worked equally on an official basis. It is shown how the division of social norms into a customary and positive law was formed, which resulted in the formation of two types of sources of law: custom and law. As the custom appears first, which is a moral norm fixed in the minds of people, and then formed, with the development of the state and society, the written law, secured by the authorized authority of the country. A separate issue in the article is considered the problems of the formation of the private property institution, as well as the formation of civil law, the creation of arbitration courts, speeches of Rome as an arbitrator in international relations. In addition to civilians, in ancient Rome, criminal law began to be formed as a means of ensuring order in society. The main principles and concepts of Roman criminal law are considered: "the principle of the talion", "the court of Lynch".